A Novel Aza-Derivative Inhibits agr Quorum Sensing Signaling and Synergizes Methicillin-Resistant Staphylococcus aureus to Clindamycin - Bernabè, Giulia; Dal Pra, Matteo; Ronca, Vittoria; Pauletto, Anthony; Marzaro, Giovanni; Saluzzo, Francesca; Stefani, Annalisa; Artusi, Ilaria; De Filippis, Vincenzo; Ferlin, Maria Grazia; Brun, Paola; Castagliuolo, Ignazio (Frontiers in Microbiology, 2021)
Increasing antibiotic resistance and diminishing pharmaceutical industry investments have increased the need for molecules that can treat infections caused by dangerous pathogens such as methicillin-resistant S. aureus (MRSA). Quorum Sensing (QS) is a signalling mechanism that regulates bacterial virulence in pathogens. A report demonstrating that the anti-inflammatory drug Diflunisal reduces MRSA virulence factors’ expression prompted us to design, synthesize and test sixteen aza-analogues as inhibitors of S. aureus virulence factors controlled by the accessory gene regulator (agr) QS system. At first, we evaluated by qRT-PCR the activity of compounds on rnaIII expression, a QS related gene. Azan-7 was the most active molecule tested and it did not show cytotoxic activity in human cell lines. Moreover, we demonstrated that it did not affect bacterial proliferation. Regulation of MRSA virulence genes by Azan-7 was investigated using qRT-PCR and RNAseq. Azan-7 significantly reduced hla, psmα, hysA, agrA, cap1A and cap1C gene expression. In silico docking demonstrated that Azan-7 binds the response regulator AgrA. This data was confirmed by electrophoretic mobility shift assay (EMSA) reporting that Azan-7 binding to AgrA protein strongly reduced the AgrA-DNA complex formation at the P3 promoter region involved in the regulation of rnaIII transcription. Azan-7 inhibited MRSA-mediated haemolysis, reduced survival of the pathogen at low pH levels, and increased macrophage killing. In addition, Azan-7 enhanced MRSA susceptibility to clindamycin both in planktonic growth and biofilm. Azan-7 did not induce resistance over ten days in culture. It was equally active against all the AgrA MRSA subtypes encountered among clinical isolates, but it was not active against S. epidermidis, although the AgrA proteins show an approximate 80% homology. These results demonstrate that Azan-7 inhibits the expression of MRSA virulence factors by interfering in the QS and synergizes MRSA biofilm with clindamycin, indicating the compound as a promising candidate for the treatment of MRSA infections.